2018
DOI: 10.1093/conphys/coy035
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the link between ultraviolet B radiation and immune function in amphibians: implications for emerging infectious diseases

Abstract: Levels of ultraviolet B radiation (UVBR), a potent immunosuppressant, have increased in parts of the world due to anthropogenic thinning of the Earth’s protective ozone layer. However, little is known about how UVBR influences amphibian immune function, or if increased UVBR exposure can contribute to disease emergence in susceptible species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 170 publications
(233 reference statements)
0
34
0
1
Order By: Relevance
“…Overexposure of frogs to UV-B radiation, in part due to deforestation and habitat loss, results in damage to the epidermal layer of larval and adult frogs (217, 218). Skin damage is characterized by epidermal shedding and sore formation, causing pronounced detrimental effects to maintenance of skin integrity and to physiological processes such as water and ion transportation (217, 218).…”
Section: Impact Of Environment On Host Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexposure of frogs to UV-B radiation, in part due to deforestation and habitat loss, results in damage to the epidermal layer of larval and adult frogs (217, 218). Skin damage is characterized by epidermal shedding and sore formation, causing pronounced detrimental effects to maintenance of skin integrity and to physiological processes such as water and ion transportation (217, 218).…”
Section: Impact Of Environment On Host Barriersmentioning
confidence: 99%
“…Overexposure of frogs to UV-B radiation, in part due to deforestation and habitat loss, results in damage to the epidermal layer of larval and adult frogs (217, 218). Skin damage is characterized by epidermal shedding and sore formation, causing pronounced detrimental effects to maintenance of skin integrity and to physiological processes such as water and ion transportation (217, 218). Though largely unexplored in frogs, it is suggested that UV radiation breaches the skin barrier and induces host immunosuppression, causing the frog to be more susceptible to both pathogen invasion and exposure to chemical contaminants, leading to host mortality (218).…”
Section: Impact Of Environment On Host Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Chytridiomycosis has been linked to the global decline and extinction of more than 500 amphibian species (Scheele et al, 2019) with many chytridiomycosisrelated declines occurring in high altitude environments (Bosch, Carrascal, Duran, Walker, & Fisher, 2007;Kriger & Hero, 2008;Lips, 1998;Middleton et al, 2001;Rohr & Raffel, 2010;Walker et al, 2010) where elevated UVBR levels (Madronich, McKenzie, Bjorn, & Caldwell, 1998) and cooler temperatures interact. In addition, many declines attributable to this disease coincide spatially and temporally with increases in UVBR associated with stratospheric ozone depletion (Berger et al, 1998;Cramp & Franklin, 2018;Lips, 1998;Lips et al, 2006;Middleton et al, 2001). Although considerable efforts have been made since the 1980s to halt the loss of UVBR-absorbing ozone, the illegal production of ozone-destroying compounds continues to hamper the recovery of the ozone layer (Ball et al, 2018).…”
Section: F I G U R Ementioning
confidence: 99%
“…Electromagnetic radiation, particularly radiation emitted from routers, affects all living systems and influences cells, tissues and organs in several ways [9] [10] [11]. They affect, for example, mammals [12]- [17], fruit flies [18], ticks [19] amphibians [20] [21] [22], ants [23], birds [24], honey bees [25] [26] [27] and protozoa [28] [29].…”
Section: Introductionmentioning
confidence: 99%